Trade Openness and Inflation Dynamics in Indonesia: Long-Run Evidence Across Four Structural Break Episodes (1969–2024) - Gde Putra Dananjaya (Journal of Economics and Business UBS, 2026)
Trade openness and its relationship with inflation dynamics have long been a crucial and extensively debated topic in the macroeconomic literature, particularly in developing economies where structural vulnerabilities make price stability a vital concern for investment and the business environment. This study empirically examines the short-run and long-run relationship between trade openness and inflation in Indonesia over the period 1969–2024, covering 56 annual observations and four major structural break episodes: the 1974 OPEC embargo, the 1998 Asian financial crisis, the 2008 global financial crisis, and the 2020 COVID-19 pandemic. Using the ARDL Bounds test, the F-bounds test confirms cointegration among the variables, with an F-statistic of 6.744 that substantially exceeds the upper critical bound at the 5% significance level. The long-run estimation yields a positive and significant coefficient on trade openness (β = 0.207, p < 0.05), which runs counter to the Romer (1993) hypothesis, indicating that greater trade exposure is associated with higher inflation in the Indonesian context. The error correction term (ECT = −1.407) is negative and significant, confirming a short-run adjustment mechanism toward long-run equilibrium. The robustness check further confirms that structural break dummies are not only theoretically justified but empirically necessary, as the long-run significance of all variables disappears entirely when dummies are excluded.